Potential pharmacologic treatments for COVID-19 patients: A review study - Cheraghi, Zeinab; Moradi, Muhammadhosein; Ziai, Seyed Ali (Student Research in Translational Medicine, 2020)
A cluster of pneumonia cases of unknown origin was detected on December 31th which led to the discovery of coronavirus disease 2019 (COVID-19). Lungs are the primary site of involvement. SARS-COV-2, which is the causative agent, enters the alveolar cells using ACE2 as a receptor. Due to exposure of first cases to Wuhan’s animal market, a zoonotic transmission was suspected. Further studies suggested human to human transmission through contact and droplets. Symptoms vary from asymptomatic to acute respiratory distress syndrome and death. Cases are diagnosed based on clinical and laboratory findings. Currently, there is no definitive treatment or vaccine and different antiviral and other treatments are being tested as possible therapeutic agents with different mechanisms, for example, Chloroquine, hydroxychloroquine, azithromycin, favipiravir, umifenovir, ribavirin, Ivermectin, etc.